The strategy of provision of CPO raw material (case study: PT. Mamuang Pasangkayu North Mamuju Regency) - Muhammad Ilham; Muhammad Arafat Abdullah; Ikrar Taruna Syah; Kasmiati Kasmiati (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
Continuity of the production process in a company will be influenced by various factors, including: capital, technology, supplies of raw materials, finished goods and labor supply. Inventory as elements of working capital is an asset that is always in a state of spinning. Supplies are also elements of seamless assets that are always considered liquid compared with other asset elements such as cash, Receivables, and marketable securities. Adequate supply of raw materials can accelerate the production process. So that the resulting finished goods can assure the effectiveness of marketing activities. PT. Mamuang Pasangkayu (North Mamuju Regency) as one of palm oil plantation management under the PT Astra Indonesia. Oil Palm Factory owned by PT Mamuang is one unit where MCC Mamuang currently acquires supplies from its core gardens and plasma gardens. PT Mamuang Pasangkayu was established in June 2006 and produced CPO/crude palm oil and PK/palm kernel. At the beginning of the factory, raw materials were obtained from several CV and Pasangkayu PTP Garden. Pt. Mamuang Pasangkayu still has constraints in its business that the production of a garden they have not enough to fulfill the needs of the factory while the supply from other gardens is not much because of the new rejuvenation process. In addition to the supply of FFB (fresh fruit bunch) acquired, since September 2007 is no longer brought to the furnace RIMDU because of consideration of large transportation costs. Moreover, changes in the CPO price in the world market also affect the number of demand and supply. Fluctuations in CPO prices affect the manufacturing process. This will also affect the amount of production produced. Price increases and price declines require rapid anticipation so that the company can adapt to the changes that occur.